Community seedbanks in protracted crisis situations: potential and challenges - Vernooy, Ronnie; Gupta, Arnab; Subedi, Abishkar; Ali Awed, Deeka; Hassan Abdi, Aidid; Saleban Jam, Mohamed; Eldie, Yahia; Jubarah, Salah; Kamilo, Solomon Swaka (2023)
This brief reviews recent initiatives to establish community seedbanks in Somaliland, South Sudan and Sudan, located in the Horn of Africa, which have paid special attention to the insecure and instable social, economic and political circumstances that affect seed and food security. Effectively functioning community seedbanks can contribute to seed security, even in a protracted crisis situation, but careful consideration should be given to community seedbank site selection, membership and decision-making, and infrastructure and equipment. Decisions about these three elements need to consider the social security situation, minimizing or avoiding the risk of people, storage facility, equipment and seeds becoming the trigger of insecurity and/or conflict.